Modelling and measuring complex impedances of power electronic converters for stability assessment of low-voltage DC-grids - Ott, Leopold; Han, Yunchao; Stephani, Oliver; Kaiser, Julian; Wunder, Bernd; März, Martin; Rykov, Kirill (2015 IEEE 1st International Conference on Direct Current Microgrids, ICDCM 2015, 2015)
Interconnecting power converters within a low voltage DC grid can be a challenging task since these devices are rarely tested under final operating conditions during their development process in conjunction with converters from different manufacturers, different kinds of loads and appropriate grid impedances. In the worst case, stationary oscillations might occur in the grid setup for which the actual reason is hard to determine and solving the problem will require time-consuming trial and error means. Therefore, theoretical knowledge about how power converters react on grid-side disturbances is crucial for a preliminary analysis of the static and dynamic performance of low-voltage DC grids before plugging the devices together. Based on these considerations general guidelines for the dimensioning of control loops and grid-side capacitors of power converters can be derived. The following outlines describe the fundamentals of power converter behavior when exposed to disturbances occurring on the output current, e. g. from load steps. Another focus lies on shaping grid-side impedances of converters to avoid stability issues. Furthermore, a method to measure the impedances of interest is thoroughly described. All obtained results are verified in a brief case study.
CRIS-Team Scopus Importer:2023-03-07
Keywords: DC Grid Stability; Grid Performance Optimisation; Measuring Complex Impedances; Power Converter Modelling